Combination effects of environmental tobacco smoke exposure and nutrients supplement during pregnancy on obesity in Chinese preschool children - Zhang, Wen-Xuan; Strodl, Esben; Yang, Wei-Kang; Yin, Xiao-Na; Wen, Guo-Min; Sun, Deng-Li; Xian, Dan-Xia; Zhao, Ya-Fen; Chen, Wei-Qing (Frontiers in Pediatrics, 2024)
Objective This study aimed to explore the combination effects of prenatal exposure to environment tobacco smoke (ETS) and nutrients supplement during pregnancy on childhood obesity in preschoolers. Methods A cross-sectional study was conducted with 58,814 child-mother dyads from 235 kindergartens in Longhua District of Shenzhen, China in 2021. A self-administered structured questionnaire was completed by mothers to collect socio-demographic characteristics, prenatal ETS exposure, and nutrients supplement in pregnancy, and preschoolers' heights and weights were measured at the same time. After controlling for potential confounding variables, logistic regression models and cross-analyses were used to examine the independent and combination effects of maternal prenatal ETS exposure and nutrients supplementation during pregnancy on obesity in preschool children. Results The results of our study showed that prenatal ETS exposure increased the risk of childhood obesity (AOR = 1.22, 95% CI = 1.11–1.34) in preschoolers. In addition, risk of childhood obesity was significantly higher when mothers didn't take supplements of multivitamins (AOR = 1.12, 95% CI = 1.05–1.20), folic acid (AOR = 1.23, 95% CI = 1.10–1.37) and iron (AOR = 1.11, 95% CI = 1.04–1.19) during pregnancy. The cross-over analysis showed that the combination of prenatal ETS exposure with mothers taking no multivitamins (AOR = 1.40, 95% CI = 1.21–1.62), no folic acid (AOR = 1.55, 95% CI = 1.12–2.14) and no iron (AOR = 1.38, 95% CI = 1.19–1.59) during pregnancy also increased the risk of obesity among Chinese preschoolers. We also discovered additive interactive effects between prenatal ETS exposure and no maternal multivitamin, folic acid and iron supplementation in pregnancy on the risk of obesity in preschoolers. Conclusion The combination of prenatal exposure to ETS with no supplementation of these nutrients might jointly increase the risk of childhood obesity. Public health interventions are needed to reduce prenatal exposure to ETS and to encourage mothers to take appropriate multivitamin, folic acid and iron supplements during pregnancy.